Political Theory of the Digital Constellation; Politische Theorie der digitalen Konstellation - Sebastian Berg; Daniel Staemmler; Thorsten Thiel (Zeitschrift für Politikwissenschaft, 2022)
The introductory contribution to this special issue on “Political Theory of the Digital Constellation” addresses the conditions and possibilities of political theory's engagement with digital developments. The motivation for this inquiry is the growing interest in questions of political theory arising from the digital transformation, as well as the acknowledgement that digitalisation not only changes politics, but conversely that politics also shapes digitalisation. The article identifies three pitfalls of previous engagement: The narrowing of the subject of “digitalisation” to the topic of the “internet” and, thereby, to the aspect of communication, the disregard for the technicality of the digital, and the insufficient recognition that (digital) technology is political. To avoid these pitfalls, the research perspective of the digital constellation is presented. The digital constellation serves as an epistemological guide that helps to structure theoretical reflection on the interrelationship between digitalisation and political questions. Ultimately, the outlines of the political theory in the digital constellation become clear in the fourteen contributions of the special volume, which are presented in conclusion. – – Der einführende Beitrag zum Sonderheft ,,Politische Theorie der digitalen Konstellation“ widmet sich den Bedingungen und Möglichkeiten der politiktheoretischen Auseinandersetzung mit digitalen Entwicklungen. Das wachsende Interesse an politiktheoretischen Fragen im Kontext der digitalen Transformation und die Erkenntnis der politischen Gestaltbarkeit von Digitalisierung, bilden den Anlass für die Beschäftigung. Der Beitrag identifiziert drei Fallstricke der bisherigen Auseinandersetzung: Die Engführung des Gegenstands Digitalisierung auf den Aspekt des Internets und damit der Kommunikation, die Missachtung der Technizität digitaler Phänomene und die mangelnde Anerkennung der politischen Aspekte von (digitaler) Technik. Um diese Fallstricke zu vermeiden, wird die Forschungsperspektive der digitalen Konstellation vorgestellt. Diese dient als erkenntnistheoretische Handreichung, um die theoretische Reflexion des Wechselverhältnisses von Digitalisierung und Politik zu strukturieren. Die Umrisse politischer Theorie in der digitalen Konstellation werden in den vierzehn Beiträgen des Sonderbands deutlich, die abschließend vorgestellt werden.
Keywords: 320; political theory; digitalisation; digital constellation; technology; epistemology; politische Theorie; Digitalisierung; digitale Konstellation; Technik; Erkenntnistheorie